Strategy To Prevent Bullying Acts In Elementary School Students At SDN 2 Lamangga Baubau City - Safaruddin Yahya; Muhamad Ridwan; Maudin; La Hanuddin; Rahmat Haniru; La Jidi; Wa Disa; Nurma (AIQU: Journal Multidiscipliner of Science, 2024)
This research aims to determine the role of the principal and all levels of teachers in the SD Negeri 2 Baubau school environment in preventing students from carrying out bullying behavior towards each other, whether intentional bullying, verbal or non-verbal. Bullying is the cause of decreased student learning achievement and results in low levels of student self-confidence. This research is field research with a qualitative approach with data collection methods, namely research field observations, interviews and documentation.  The subjects studied were students in grades V and VI at SDN 2 Lamangga. The results of the research show that the school implemented five strategic steps as an effort to prevent bullying in the school environment, including; 1) provide an explanation to students regarding the impact of bullying which will be experienced directly by the victim, 2) build the perception that all students are equal in social status, 3) Provide punishment for bullying behavior directly, 4) Give rewards to students for speaking politely, 5) instill a sense of caring for fellow students.